Much Lost, Little Gained? Contemporary Trade Agreements in the Pacific Islands. Issue 3 (3rd July 2018) - Morgan, Wesley
ABSTRACT: At the close of the 20th century, it was increasingly clear that Pacific Island countries would struggle to remain competitive in international commodity and merchandise trade. As governments worldwide embraced free trade, many Island exporters looked set to be displaced by more efficient producers elsewhere. Island policymakers also faced pressure from more powerful states to renegotiate trading arrangements to bring them into alignment with the rules of the World Trade Organization. This article explains how Pacific Island countries responded to the overlapping challenges of globalization. It considers strategies pursued by Island states in negotiations with the European Union (EU), and with Australia and New Zealand. In both cases, Pacific Islands pressed for agreements that would take account of their unique trading circumstances, and arrangements that would allow more Pacific Islanders to work abroad. After nearly two decades of talks, however, final results proved disappointing. A proposed regional Economic Partnership Agreement with the EU was essentially abandoned, and a regional trade agreement with Australia and New Zealand was concluded without the signature of Fiji or Papua New Guinea – the two largest Pacific Island economies. Ultimately, contemporary trade agreements in the Pacific achieved little to ameliorate the competitive disadvantages Pacific Island states face participating in international trade.